Strength, efficacy and tolerability of morphine solution with and without added preservatives: A comparative study (Bangladesh Journal of Pharmacology, 2015)
Cancer patients having moderate to severe pain need immediate pain relief. Immediate release formulation of morphine is not available in Bangladesh. This open label randomised two phase crossover clinical trial was conducted to compare strength, efficacy, and tolerability of oral morphine solution prepared from morphine sulfate injectable formulation and sustained release tablet with and without added preservatives. Concentration of morphine in solutions both with and without added preservative was highest on the first day and then gradually decreased. No difference between two storage temperatures on first day, but highly significant difference afterwards. Rate of degradation of morphine in solution with added preservative was significantly slower. The present study revealed that the solutions prepared from sustained release tablets and injectable formulation with added preservative could be an option to control severe pain in cancer patients. To introduce the present research finding in clinical practice, this has to be accepted institutionally.